World Politics in Colour. (June 2017) - Ling, L. H. M.
Racism reflects how we think and act as much as what. It manifests in terms of biology, geography, and culture but reflects an episteme that normalises Self and Other into a bordered binary. Here, a trialectical epistemology can help. It dissolves racialised realities by showing how opposites exist in each other, thereby constituting a three-ness – e.g. self-in-other and other-in-self – that links Self and Other despite mutual antagonisms. From such trialectics, epistemic compassion can arise. It enables learning from the Other through what Buddhists call 'interbeing' or the recognition that 'you are in me, and I in you'. Reciprocity thus becomes key. The Self cannot violate the Other without also violating itself; likewise, loving the Other effectively loves the Self. Flat, monochromatic binaries like 'black' versus 'white' cannot continue and colour revivifies world politics, both literally and figuratively. I apply trialectics to the 'border problem' between India and China as an analogy.